Pendampingan Pengelolaan Desa Wisata Watugede Untuk Meningkatkan Kesejahteraan Masyarakat - M Soleh Mauludin; Khurun’in; Saidul Hafizi; Muhammad Bayu Fikrul Khoir; Tia Nurhidayah; Hana Mariska Dewi; Chumidatus Sa'diyah; Nilna Fatikhatul Husna; Alfinafristi Damayanti; Saila Rizka Kamila (LP3M IAIFA Kediri, 2025)
One strategy to improve community welfare is to develop MSMEs and utilize various media, both digital and print, as promotional tools. MSMEs have a major contribution to the local economy, especially in Watugede Village which has natural resource potential, such as the Watugede Raya Embung. This research uses the Asset-Based Community Development (ABCD) approach, which places the community as the main actor in managing village potential. The